CONSUMER PREFERENCE AND ITS INFLUENCE ON BRAND POSITIONING (International Seven Journal of Multidisciplinary, 2025)
The positioning of a brand is supported in the opinions of consumers. It is clear that advertising can influence positively so that this aspect is developed. However, there are other aspects such as its content, the way of communicating a message, and in particular that the programme will reach the audience to which it is addressed this allow a television program to improve their positioning. In this research the results of an investigation are presented to study the perceptions of viewers of the program youth without DNA which is broadcast by Regional Television ORT channel and which is aimed at a young audience. Constituted the sample 94 viewers, those who follow the channel, and who, from their responses, managed to position the brand in the measurement of ratings in Colombia showing a notable improvement in the growth of audience connected with the program in his hour of emission. The main finding of this research is to determine a schedule suitable for the issuance of the youth program, identifying the best time to get the program to its target. In addition, demonstrate the remarkable growth that the program managed to have after this wise decision, have national recognition. At the end we propose alternatives for the development of disruptive content with the purpose of not only being one of the most watched by the young audience but have a recognition awards India Catalina as the best youth program in the country.